(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We perform an investigation using numerical simulations to examine the influence of magnetohydrodynamics and thermal radiation on the mass transport and thermal energy properties of non-Newtonian Reiner-Philippoff nanofluids. We thoroughly examine the species response concerning activation energy, thermal radiation at the surface, viscous dissipation, Cattaneo-Christov double diffusions, and mass and energy transfer. This analysis also examines the impacts of an applied transverse magnetic field and Ohmic heating. Using appropriate similarity variables converts the specified governing system of PDEs into a non-linear system of ODEs. We numerically solve the governing equations using the Mohand transform (MT) in conjunction with the Adomian decomposition method (ADM). The sophisticated Modified Decomposition Method (MDM) streamlines complex equations for computational solutions. It uses ADM and the MT to make sure that the series converges, giving a solution very close to the exact solution. We illustrate the temperature, species distributions, and flow velocity for the relevant parameters governing the Reiner-Philippoff model on two-dimensional charts to understand the influence of dimensionless parameters on these values. The tabulation, depiction, and interpretation of the local Nusselt number, local Sherwood number, and skin friction coefficient exemplify further engineering inquiry. We have utilized a table to illustrate the concordance between the current numerical data and previously published findings.